PENGARUH MOTIVASI BELAJAR TERHADAP TINGKAT KEHADIRAN SISWA KELAS VIII SMPN 3 ROGOJAMPI - Dwi Ayu Maulidia; Heribertus Wicaksono; Siti Napisah (CV. Lafadz Jaya, 2026)
Student attendance is an important indicator of academic engagement, learning discipline, and readiness to participate in school activities. This study aimed to describe students' learning motivation, describe students' attendance level, examine the influence of learning motivation on attendance, and identify the contribution of learning motivation in explaining variations in the attendance of eighth-grade students at SMPN 3 Rogojampi. This research employed a quantitative correlational design. Learning motivation data were collected using a 35-item Likert-scale questionnaire from 154 respondents, while attendance data were obtained from official school attendance documentation for the even semester. A total of 148 matched cases were included in the advanced analysis. The data were analyzed using descriptive statistics, Pearson correlation, Spearman correlation, and simple linear regression. The results showed that students' learning motivation was in the high category, with a mean score of 130.773. The average total absence was 9.162 days. Pearson correlation produced r = -0.029 with Sig. = 0.726, while Spearman correlation produced rho = -0.090 with Sig. = 0.279. The regression result showed R Square = 0.001, or approximately 0.08%. Therefore, learning motivation was not proven to have a significant influence on student attendance. These findings indicate that attendance improvement requires guidance and counseling services that address not only learning motivation but also family, health, self-discipline, and school-environment factors.